PENGARUH PENGGUNAAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPA TERPADU DI KELAS VIII MTSN 1 KOTA MAKASSAR - Diana Ariyana; Safei Safei; Marjuni Marjuni (Al-AHYA: Jurnal Pendidikan Biologi, 2019)
This study discusses the influence of learning strategy of improving thinking ability (SPPKB) one student learning outcomes in integrated science lesson in class VIII MTsN 1 Makassar city. The purpose of this research is to know the learning result of the students in class VIII MTsN 1 makassar city taught by using the learning strategy of thingking ability improvement (SPPKB) in integrated science lesson, to know the learning result of the students in class VIII MTsN 1 makassar city is taught without using learning strategy to improve thinking ability (SPPKB) in integrated science lesson, and to know the influence of learning strategy of improving thinking ability (SPPKB) toward student learning outcomes in integrated  science lesson in grade VIII MTsN 1 makassar city. This research is experimental of quasi experiment form (Quasi Experimental), pretest-posstest control group design is research design. All students of class VIII MTsN makassar city is the population of this research. And the sample of this study is class VIII 12 (Experiments) with the number of 39 students and VIII 11 (Control) with the number of 40 students. Data retrieval is done by using learning result test in the form of pretest and posstest, analysis technique in this research is descriptive and inferential analysis tecnique. The result of research indicate the influence of learning outcomes who were taught using learning strategy to improve thinking ability (SPPKB) on plant body structure material in class VIII MTsN 1 makassar city karena H0 rejected and H1 accepted. Seen from analysis of the value tarithmetic 1,708  and value ttabel 1,664 from value dk=n-1 (79-1) so value tarithmetic > ttabel thats is (1,708>1,664).